THE FUNCTION OF SOCIAL MEDIA AS A SUPPORTING TOOL FOR LECTURER CAREER DEVELOPMENT IN UNIVERSITIES IN THE INDUSTRY 4.0 ERA - Ali Ibrahim; Rahmat Izwan Heroza; Iredho Fani Reza; Mira Afrina; Yadi Utama (LPPM Nusa Mandiri, 2023)
Lectures have many duties. The most important one is to implement the tri-dharma of higher education (teaching, research and community service). One of the efforts to support these duties in the Industry 4.0 era is the use of social media to develop professors' careers. A lack of understanding of the role of social media sometimes only sees the dark side of social media, which is actually very useful in developing lecturers' careers. This study uses a qualitative research method with a narrative research design. The subjects of this study were 92 individuals identified through purposive sampling technique. Data collection was done through an online survey. Data analysis in this study used coding techniques consisting of open coding, axial coding and selective coding stages. The findings of this study show that social media is a professional development tool for teachers and can enhance professional competence, which can contribute to teachers' professional development. Professional development that enhances the performance of the Tri Dharma of Higher Education in the areas of teaching, research and community service.